Discourse Markers in Muniba Mazari’s “We All are Perfectly Imperfect” Speech (2017) - Suprihatiningsih Suprihatiningsih; Christina Christina (Metaphor, 2021)
This article presents the discourse markers used in speech. It applies qualitative research methodology while analyzes the discourse markers using discourse markers approach. Our aims are to analyze the types of discourse markers based on Biber’s theory and to analyze the functions of discourse markers based on Schiffrin’s theory that found in the speech entitled “We All Are Perfectly Imperfect” (2017). The result shows that there are ten types of discourse markers, five of which are linking adverbials, answer forms, stance adverbials, answer elicitors, and interjections. The linking adverbials dominates the types of discourse markers used by Muniba Mazari in her speech, while interjection is the least-used type. Furthermore, six discourse marker’s functions are found in this speech. Three of them are Marker of Connectives, Marker of Information and Management, Marker of Response. The most distribution of discourse markers’ function is marker of connectives and the fewest is marker of temporal adverb.